2005
DOI: 10.1159/000086333
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Tolerance between Unmodified and High Doses of Chemically Modified Allergen Vaccines of <i>Dermatophagoides pteronyssinus</i>

Abstract: Background: The physiochemical modification of allergens to reduce allergenicity, while retaining immunogenicity, provides a chance for the administration of higher doses of immunotherapy, with a decreased risk of systemic reactions. Objective: To evaluate the safety of doses of depigmented glutaraldehyde-polymerized vaccine of Dermatophagoides pteronyssinus increasing those used in normal clinical conditions in comparison with regular doses of a non-modified vaccine. Materials and Methods: The study was doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 44 publications
4
38
0
Order By: Relevance
“…In patients with respiratory allergy submitted to SCIT with depot extracts there were no evident differences connected to the extract composition, either mites or pollens. Regarding the allergoid extracts, a reduced inflammatory activity was observed at the administration site, similarly to what was previously reported in the literature and demonstrated in daily clinical practice (Casanovas et al, 2005(Casanovas et al, , 2007Ariano et al, 1999). The modification of the allergenic with glutaraldehyde reduced the local inflammatory activity to levels similar to the ones observed in the control patients submitted to SS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In patients with respiratory allergy submitted to SCIT with depot extracts there were no evident differences connected to the extract composition, either mites or pollens. Regarding the allergoid extracts, a reduced inflammatory activity was observed at the administration site, similarly to what was previously reported in the literature and demonstrated in daily clinical practice (Casanovas et al, 2005(Casanovas et al, , 2007Ariano et al, 1999). The modification of the allergenic with glutaraldehyde reduced the local inflammatory activity to levels similar to the ones observed in the control patients submitted to SS.…”
Section: Discussionsupporting
confidence: 86%
“…The aqueous extracts are highly effective, but induce more side-effects (local and systemic) than depot and modified vaccines (Larché et al, 2006). These have been developed in an attempt to reduce or remove allergenicity, while preserving or increasing the immunogenicity (Casanovas et al, 2005). Aqueous subcutaneous SIT is now the gold standard treatment for hymenoptera venom allergy and depot aeroallergen extracts for respiratory allergy (Wheeler & Woroniecki, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These extracts have shown efficacy using objective parameters, such as specific bronchial provocation and skin tests, demonstrating improvement after 6 months of treatment [22] or after 4 months when a shorter build-up schedule (cluster) was used [23]. They also have a wider safety profile than unmodified preparations since doses greater than those recommended can be administered without moderate or serious adverse reactions [24]. …”
Section: Discussionmentioning
confidence: 99%
“…The introduction of a depigmentation step, before the polymerization process removes the adsorbed pigments, enhances the solubility of the allergoids and inactivates the enzymatic activity [18]. These recently developed allergoids have been used in clinical studies of efficacy, safety and tolerability [19,20,21,22,23,24,25,26]. These vaccines maintain or increase IgG recognition, while significantly reducing IgE reactivity, which allows shortening of the build-up phase and the administration of higher doses than those used with non-modified allergens.…”
Section: Introductionmentioning
confidence: 99%
“…Although the efficacy of this approach for the treatment of rhinoconjunctivitis and asthma has been confirmed in many controlled studies [2,3], conventional subcutaneous immunotherapy involves injection of allergen extracts with the potential to cause severe allergic reactions due to cross-linking of allergen-specific IgE. This small risk of anaphylaxis has limited the use of subcutaneous immunotherapy and led to the development of modified allergen extracts, termed allergoids, with reduced IgE-binding activity (allergenicity) [4], thus increasing safety [5]. On the other hand, although not many studies have analyzed T cell reactivity (immunogenicity), some studies have suggested that reactivity of T helper cells with allergoids is dependent on the type of antigen-presenting cells [6] and the individual [7].…”
Section: Introductionmentioning
confidence: 99%